A child-rights analysis of selected United Nations treaty body jurisprudence to inform the emerging jurisprudence under the third optional protocol to the convention on the rights of the child - Skelton, Ann, 1961- (University of Pretoria, 2023)
Thesis (PhD (International Children’s Rights))--University of Pretoria, 2022.